Analysis Of The Influence Of Operating Cash Flows And Accounting Profit On Stock Returns In Lq-45 Companies Listed On The Indonesia Stock Exchange (IDX) For The 2018-2020 Period - Ediman Imani Hati Halawa (Lembaga Penelitian dan Pengabdian Kepada Masyarakat-Universitas Darma Agung. (LPPM_UDA), 2023)
The importance of stock returns for investor because it is one of the factors that motivate investors to invest and is a form of reward and investor courage in taking risks, The main concern of investors in a company is to analyze financial statement especially accounting profit and operating cash flow. This study to determine the effect both simultaneously and partially between operating cash flow, accounting profit to stock return on LQ45 Companies listed in periode 2018-2020. The data in this researc is secondary data obtained from the company’s annual finnacial statement in the Indonesia Stock Exchange (IDX) or www.idx.co.id. This type of research is quantitative. The sampling technique used is purpusive sampling, This research has a population of 45 companies and 23 research samples. The data analysis technique used is descriptive statistics, classical assumption test, and multiple linear regression Analysis. Based on partial hypothesing testing operating cash flow has a thang value t value 1,468< t table1,670 with a sing value of 0,145>0,05 while accaumtimg profit has a thining t value 2,458>t table 1,670 with a sing value of 0,015<0,05 and ssimultaneous hypothesis testing F value 4,010>F table 3,14 with a significance value of 0,021<0,05. It can be concluded that operating cash flow has no significant effect on stock return and accounting profit has a significant effect on stock returns. Based on simultaneous hypothesis test or F test concluded that operating cash flow and accounting profit have a significant effect on stock returns.